2018
DOI: 10.3892/or.2018.6647
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of BEX1 predicts poor prognosis in patients with esophageal squamous cell cancer

Abstract: The brain expressed x‑linked gene 1 (BEX1) is a member of the BEX family and is aberrantly expressed in many cancers. However, the clinical significance of BEX1 expression level and its role in the pathology of esophageal squamous cell cancer (ESCC) remain unknown. In the present study, we determined BEX1 expression in the tumor and adjacent normal tissues from 118 ESCC patients by immunohistochemistry and determined the proliferation and growth of ESCC cells following ectopic overexpression of BEX1 in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Regulator of G protein signaling 6 (RGS6), which is down-divergent in most tumor samples, has been observed to be a suppressor of breast cancer [19]. BEX1 has been linked to ER+ breast cancer (a greater proportion of ER+ samples are divergent compared to ER− samples), as well as acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and squamous cell cancer [2022]. The human protein atlas data suggests PROZ as a prognostic marker in liver cancer, with higher protein expression observed in a subset of breast cancer samples [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Regulator of G protein signaling 6 (RGS6), which is down-divergent in most tumor samples, has been observed to be a suppressor of breast cancer [19]. BEX1 has been linked to ER+ breast cancer (a greater proportion of ER+ samples are divergent compared to ER− samples), as well as acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and squamous cell cancer [2022]. The human protein atlas data suggests PROZ as a prognostic marker in liver cancer, with higher protein expression observed in a subset of breast cancer samples [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, BEX1 was confirmed as a target of miR-5581-3p in glioma. BEX1 belongs to the BEX family and is found abnormally expressed in cancers [13][14][15]. For example, low BEX1 was identified in esophageal squamous cell cancer and significantly correlated with large tumor size and late tumor stage [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel biomarkers for the detection and prognosis evaluation of LUAD are required. Previous studies have revealed that the BEX family may serve roles as predictive biomarkers in tumors, such as esophageal squamous cell cancer and acute myeloid leukemia (12,40). The potential clinical value of the BEX family members in LUAD warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that low expression of BEX1 was associated with clinicopathological characteristics such as tumor volume, T stage and clinical stage in esophageal squamous cell cancer (12). The present study investigated the association between the expression of the BEX family and the clinicopathological features of patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation